Comparing analytical hierarchy process (AHP) and likert scale - Nur Najihah, Bakri (2019)
The construction industry in Malaysia is one of the first sectors of national economy. During era of economic growth in Malaysia’s development, the benefaction of construction industry to gross domestic product (GDP) is in the range of 3%-6% per year. For eight years from year 1989 to year 1996, the construction industry has recorded double-digit growth rates. The development of the construction industry is directly proportional to the national economy. In construction project, contractor role is important to ensure that the project will be able to deliver on time and within the budget cost with a good quality. Thus, the contractor selection plays important role in construction industry successfulness. In this study, a questionnaire survey is carried out to determine the main criteria for contractor selection in Malaysia. In this research, two methods were used which are Analytical Hierarchy Process (AHP) and Likert Scale to compare whether the results would be different in both methods. Both of this method are decision-making process that is obligatory to eliminate the risks of project failure due to poor contractor’s performance.